Sinergi Akuntansi dan Literasi Bahasa dalam Optimalisasi Leadership dan Administrasi Keuangan Organisasi Siswa Intra Sekolah (OSIS) untuk Meningkatkan Profesionalisme Organisasi Siswa - Aden Apandi; Muzzamilah Zamil; Yusufi Arif Mustafa (LPMP Imperium, 2026)
The training activity for strengthening the capacity of student council (OSIS) members at MA Sirojul Athfal 2 and MTs Sirojul Wildan was conducted to enhance students’ understanding, skills, and motivation in organizational management. The program emphasized leadership concepts, organizational management, and practical preparation of work programs aligned with school needs. Evaluation was carried out through participant observation and satisfaction questionnaires. Results showed that more than 80% of participants were actively engaged in discussions, questions, and opinion sharing. Additionally, the questionnaire revealed an average satisfaction rate of 87%, confirming that the training content was relevant and beneficial to support OSIS performance. Participants also suggested follow-up activities such as financial report workshops and leadership simulations. Therefore, the training is concluded to be effective in improving OSIS members’ organizational capacity. Future programs are recommended to expand more practical materials so that participants can directly apply their knowledge in organizational settings.